2022
DOI: 10.2217/cer-2021-0242
|View full text |Cite
|
Sign up to set email alerts
|

Impact of telehealth on health care resource utilization during the COVID-19 pandemic

Abstract: Aim: To assess healthcare utilization (HCRU) among patients with incident telehealth visit during the COVID-19 pandemic. Materials & methods: Retrospective pre-post analyses was conducted using HealthJump data. Adults continuously enrolled with an incident telehealth visit between Feb and April 2020 were identified. Demographics, clinical characteristics, proportion of patients with ≥1 HCRU visits and post-index trends in HCRU were analyzed. Results: Sample constituted 2799 patients, 60.34% female and 46.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…A recent study found an increase in outpatient visits after receiving telehealth [ 31 ]. They found a significant increase (5.36%) in the proportion of established patients with OP visits during the pandemic for the overall sample compared to the pre-pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found an increase in outpatient visits after receiving telehealth [ 31 ]. They found a significant increase (5.36%) in the proportion of established patients with OP visits during the pandemic for the overall sample compared to the pre-pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, our slightly larger findings (approximately 15%) may be explained as we included a control group that accounted for the more limited number of OP visits available during the pandemic period. Another study also found telehealth users had more in-person outpatient visits than non-telehealth users; it was conducted among Medicare beneficiaries with type 2 diabetes [ 27 ]. These findings indicate that telehealth is a promising approach to maintain contact between patients and physicians, which could promote more in-person outpatient visits for needed care or examinations.…”
Section: Discussionmentioning
confidence: 99%
“…With the ever growing pressure on hospital systems to reduce cost of care, telehealth may help improve clinical efficiency without compromising quality of care. 62 In Otolaryngology as well as other specialties, telehealth visits have been shown to decrease office visit cycle time, defined as the time that a patient spends at a visit, when compared to in-person visits. 52 , 63 , 64 Moving forward, incorporation of telemedicine into the workflow of healthcare systems is key to transitioning current practices into a sustainable patient care model.…”
Section: The Future Of Telehealthmentioning
confidence: 99%
“…Little is also known about the effect of telehealth on resource utilization. Arora et al reported a significant increase in prescription use during telehealth care but not specifically for the treatment of diabetes and obesity 5 . Telehealth implementation in an adolescent bariatric surgery program led to an increase in attendance rates (83.1% vs. 70.5%) and a reduction in cancellation rates (9.9% vs. 22.5%) compared to in‐person appointments 6 .…”
Section: Introductionmentioning
confidence: 99%